GEOCHEMICAL RESEARCHES OF SOILS OF THE NATURE PROTECTION OBJECTS OF THE EASTERN PART OF SOUTH BANK OF CRIMEA - Kuraieva, I.; Loktionova, E.; Manichev, V.; Guschina, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Data of the regularity distribution of the chemical elements in the soilforming rocks, soils and plants of the reserved zones of eastern part of south coast Crimea were putting.